Spectral response of Chlamydomonas reinhardtii using light-emitting diodes - Wu, B. S.; Loganathan, B. G.; Galan, A.; Raghavan, V.; Orsat, V.; Lefsrud, M.
Algal cultures produce high yields for a myriad of applications because of their rapid growth and chemical constituency. The fast-paced and ongoing development of more energy efficient and wavelength-specific light-emitting diodes (LEDs)opens interesting possibilities in the development of wavelength-specific systems for propagating different photosynthetic organisms. However, not all wavelengths and intensities are effective and practical for algal growth. In this study, we investigated the action spectrum (spectral photosynthesis)of Chlamydomonas reinhardtii using narrow-spectrum LED light at different PPFD levels (50, 100, and 150 ?mol m-2 sec-1). Data indicate that increased light intensity led to shifting in peak wavelengths of action spectra and reduction in photosynthetic rates. Blue and red lighting were the most efficient light wavelengths for algal photosynthesis, yet this phenomenon only occurred at low and medium light levels. The 600-nm LED light induced the highest photosynthetic activity at 150 ?mol m-2 sec-1 and a reduction in photosynthetic rates (10 to 60 percent ) was observed while increasing light intensity for all experimental wavelengths. The findings in this work clearly demonstrated that both light wavelength and intensity greatly impact Chlamydomonas photosynthetic activity, and that the interactive effect between light wavelength and intensity should be considered when optimizing algal growth. Findings provided information on photosynthetic activity of algae growth with respect to specific wavelengths and intensities, with the possibility of improving algal growth under narrow-spectrum lighting environment.
Keywords: ACTION SPECTRUM; ALGAL GROWTH; CHLAMYDOMONAS REINHARDTII; LED; LIGHT INTENSITY; WAVELENGTH